Aktywność fizyczna osób z przewlekłym wirusowym zapaleniem wątroby typu C - Kowalska, Marta Estera; Kalinowski, Paweł; Bojakowska, Urszula (Journal of Education, Health and Sport, 2016)
Kowalska Marta Estera, Kalinowski Paweł, Bojakowska Urszula. Aktywność fizyczna osób z przewlekłym wirusowym zapaleniem wątroby typu C = Physical activity of people with chronic hepatitis C. Journal of Education, Health and Sport. 2016;6(2):275-282. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46660 http://ojs.ukw.edu.pl/index.php/johs/article/view/3402 https://pbn.nauka.gov.pl/works/717152 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016. Aktywność fizyczna osób z przewlekłym wirusowym zapaleniem wątroby typu C Physical activity of people with chronic hepatitis C Marta Estera Kowalska, Paweł Kalinowski, Urszula Bojakowska Samodzielna Pracownia Epidemiologii Uniwersytetu Medycznego w Lublinie Independent Epidemiology Unit, Medical University of Lublin Słowa kluczowe: wirusowe zapalenie wątroby typu C, aktywność fizyczna, edukacja zdrowotna. Key words: hepatitis C, physical activity, health education. Streszczenie Wstęp Wirusowe zapalenie wątroby typu C stanowi jeden z głównych problemów zdrowia publicznego ze względu na długi okres bezobjawowy zakażenia wirusem HCV (hepatitis C virus) oraz brak skutecznej szczepionki. Cel pracy Celem pracy była ocena poziomu aktywności fizycznej u osób z przewlekłym wirusowym zapaleniem wątroby typu C. Materiał i metody Materiałem wykorzystanym do badań były odpowiedzi na pytania zamknięte zawarte w autorskim kwestionariuszu ankiety. W badaniu wzięło udział 200 osób z potwierdzonym zakażeniem HCV. Wyniki Większość badanych podejmuje aktywność ruchową kilka razy w roku lub też sezonowo. Stwierdzono również, iż w badanej grupie im starszy wiek tym ankietowani rzadziej deklarują podejmowanie form aktywności fizycznej. Ponadto wykazano, iż aktywność fizyczna zmienia się wraz z poziomem wykształcenia. Im wyższy poziom wykształcenia, tym badani częściej podejmują aktywność fizyczną. Wnioski W grupie badanych pacjentów z wirusowym zapaleniem wątroby typu C występuje niska częstotliwość podejmowania aktywności fizycznej. Tylko młodzi ludzie oraz posiadający wyższe wykształcenie deklarują aktywność fizyczną prowadzoną kilka razy w roku. Abstract Introduction and aim: Hepatitis C is one of the major public health problems due to the long period of asymptomatic infection with HCV and the lack of an effective vaccine. The aim of this study was to evaluate the level of physical activity in patients with chronic hepatitis C. Materials and methods: Material used for the study were responses to closed questions contained in the author’s survey interview. The study involved 200 people with confirmed HCV infection. Results: Most of the respondents take physical activity several times a year or seasonally. It was also found that in the group of the older age of the respondents declare less likely to take forms of physical activity. In addition, it has been shown that physical activity varies with level of education. The higher the level of education, the subjects often take physical activity. Conclusions: The study group of people with hepatitis C has a relatively low frequency of making physical activity. Only young people and with a higher education declare frequent physical activity than a few times a year.